1912 N.J. Laws 364 - (:unkn) unknown (My University, 1912)
Ch. 225, 1: Any person who shall carry any revolver, pistol, firearm, bludgeon, blackjack, knuckles, sand-bag, slung-shot or other deadly, offensive or dangerous weapon, or any stiletto, dagger or razor or any knife with a blade five inches in length or over concealed in or about his clothes or person, shall be guilty of a misdemeanor
Keywords: CARRY - CONCEALED